Divide and Rule, Unite and Resist: Contact, Collective Action and Policy Attitudes among Historically Disadvantaged Groups. (September 2015) - Dixon, John; Durrheim, Kevin; Thomae, Manuela; Tredoux, Colin; Kerr, Philippa; Quayle, Michael; Stroebe, Katherine; de Lemus, Soledad
<x xml:space="preserve">Abstract</x> Racial segregation encourages members of historically advantaged groups to form negative intergroup attitudes, which then motivate practices of discrimination that sustain inequality and disadvantage. By implication, interventions designed to increase intergroup contact have been proposed as a means of reducing dominant group prejudices and promoting social change. In this article, we highlight another mechanism through which segregation shapes intergroup relations, namely, by inhibiting political solidarity between historically disadvantaged groups. Building on a field survey conducted in postapartheid South Africa, we demonstrate how challenging this form of segregation may reveal alternative mechanisms through which intergroup contact facilitates social change. Notably, we report evidence that positive contact with Black residents of an informal settlement in Pietermaritzburg was associated with Indian residents' support for political policies and forms of collective action that might improve conditions in that settlement. In addition, we show that such support was partly mediated by perceptions of collective discrimination.